(untitled) (Fiep Bulletin - online, 2014)
In recent times there has been a growing preoccupation among international organizations in public health concerning: the sedentary life style and the increase in the number of chronic non transmissible types of pathologies (coronary obstruction, vein obstruction and stress among others). Base on this information the object of this research was to verify the life style of those working in the municipal Post Office in Fortaleza. By applying the questionaire of the five point diagram of well being as elaborated by NAHAS, 2001, which consists of an analysis of five topics in relation to the quality of life. Based on a statistical analysis of the data that came to light, it was discovered that it is imperative to better nutritional components and physical activity, as these two items obtained the lowest scores in the research.